Boundary Spanning Elements and the Marketing Function in Organizations: Concepts and Empirical Studies - Sahadev, Sunil (Springer, 2015)
This book presents current research on boundary spanning elements. The editors bring together extant knowledge in the field and present a uniform narrative. Previous studies have often been disseminated across several academic disciplines like services marketing, personal selling and sales management etc. and this monograph aggregates studies dealing with boundary spanning elements or has boundary spanning elements related to the marketing function as the main empirical platform under a uniform theoretical perspective. Each chapter in the book deals with an important research theme and synthesizes studies in relation to boundary spanning elements.